High-speed feedback based wavefront shaping for spatiotemporal enhancement of incoherent light through dynamic scattering media - Hsieh, Chao-Mao (2023)
Feedback-based wavefront shaping is a promising and versatile technique for enhancing the contrast of a target signal for both coherent and incoherent light through a highly scattering medium. However, this technique can fail for a dynamic sample with a short correlation time. So far, most proposed methods for high-speed wavefront shaping can only directly enhance the intensity of coherent light but not incoherent light. Here we try to fill this gap to directly enhance incoherent light with high speed, such as fluorescence, which is essential in extending wavefront shaping to biomedical applications. For this purpose, we develop a technique based on a single acousto-optic deflector (AOD) with field-programmable gate array (FPGA) acceleration for spatiotemporal focusing within milliseconds. With the digital time gating of the feedback signal, spatiotemporal focusing of laser light with high contrast can be formed behind dynamic scattering media in milliseconds resulting in fluorescence enhancement. Furthermore, FPGA-based wavefront shaping is shown to effectively enhance fluorescence directly behind dynamic samples with short correlation times.